One-dimensional helical aggregates organized from achiral imine-based polymers - Liu, Guofeng (2022)
Organizing synthetic polymers, especially achiral polymers, into one-dimensional helical nanoarchitectures is challenging, which typically relies on pre-existing templates, such as properly folded DNA or polypeptide chains. Herein, we show that sonication-assisted self-assembly of achiral polymers linked by imine bond can self-organize into helical nanofibers, as proven from scanning electron microscopy and spectroscopy techniques. A systematic study of various imine-linked polymers reveals that the helical nanofibers are generated through the ∝-πstacking of adjacent polymers under the assistance of sonication rather than the influence by the topological structures of polymers and solvent context. The approach developed in this work may facilitate the access to previously inaccessible helical aggregates and promote the design of helical nanostructures from achiral building blocks in nanofabrication and nanoengineering.